Representasi Bullying dalam Drama Korea Pyramid Game: Analisis Semiotika Roland Barthes - Anggit Sabrina; Arief Hidayatullah; Rahmi Rahmi (Yayasan Literasi Sains Indonesia, 2025)
Mass media has undergone rapid development and plays a significant role in shaping public perceptions through various forms of content, including television dramas. One notable example is Pyramid Game, a Korean drama that highlights the phenomenon of Bullying within the school environment by symbolizing power structures and social inequality. This study aims to identify the representation of Bullying in Pyramid Game by applying Roland Barthes’ semiotic approach. This approach serves to analyze visual and narrative elements that convey denotative, connotative, and mythological meanings within the context of physical, verbal, psychological, and cyber forms of violence. Data were collected through observation techniques by watching and analyzing Pyramid Game, followed by selecting specific scenes for deeper analysis. Through Roland Barthes’ semiotic framework, the analysis reveals that Pyramid Game represents Bullying, categorized into four types: physical Bullying, verbal Bullying, psychological Bullying, and cyberBullying, as a form of power within a hierarchical social system.